A Structured Monodisperse PEG for the Effective Suppression of Protein Aggregation1. Issue 9 (30th January 2013) - Muraoka, Takahiro; Adachi, Kota; Ui, Mihoko; Kawasaki, Shunichi; Sadhukhan, Nabanita; Obara, Haruki; Tochio, Hidehito; Shirakawa, Masahiro; Kinbara, Kazushi
<x xml:space="preserve">Abstract</x> Part of the solution: A PEG with a discrete triangular structure exhibits hydrophilicity/hydrophobicity switching upon increasing temperatures, and suppresses the thermal aggregation of lysozyme to retain nearly 80 % of the enzymatic activity. CD and NMR spectroscopic studies revealed that, with the structured PEG, the higher‐order structures of lysozyme persist at high temperature, and the native conformation is recovered after cooling.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>